PEDAGOGICAL-PSYCHOLOGICAL FEATURES OF THE CONTENT OF THE FEELING OF TOLERANCE OF PRIMARY SCHOOL STUDENTS IN MUSIC LITERACY LESSONS. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the pedagogical and psychological foundations for developing the feeling of tolerance in primary school students during music literacy lessons. It emphasizes how music, as a universal language, can serve as an effective medium to cultivate tolerance, respect, and emotional intelligence among children. The article examines the content, teaching strategies, and classroom environment that promote inclusivity and cultural understanding. Based on the analysis of literature and practical observations, the study provides a model of implementing tolerance-building practices in music education and discusses its significance in early childhood social development.